The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2014
DOI: 10.1161/hypertensionaha.114.03953
|View full text |Cite
|
Sign up to set email alerts
|

Allopurinol Initiation and Change in Blood Pressure in Older Adults With Hypertension

Abstract: H yperuricemia is associated with incident hypertension, 1 and preclinical studies support a role for hyperuricemia in the development of hypertension. Hyperuricemia has been shown to raise blood pressure (BP) in normotensive rats, and this rise is attenuated by urate-lowering drugs.2 Furthermore, sustained hyperuricemia has been shown to induce a primary renal arteriolopathy and a salt-sensitive rise in BP in experimental models. Recently, randomized placebo-controlled and blinded clinical trials have shown t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
33
0
7

Year Published

2016
2016
2021
2021

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 58 publications
(43 citation statements)
references
References 26 publications
3
33
0
7
Order By: Relevance
“…This is consistent with previous studies, which have shown a doseresponse relationship in relation to effects on endothelial function 9 and clinical end points. 26 Allopurinol is associated with a risk of significant side effects although seems to be generally well tolerated 27 including at higher doses ≤600 mg in recent studies.…”
Section: Dose-dependent Responsesupporting
confidence: 93%
“…This is consistent with previous studies, which have shown a doseresponse relationship in relation to effects on endothelial function 9 and clinical end points. 26 Allopurinol is associated with a risk of significant side effects although seems to be generally well tolerated 27 including at higher doses ≤600 mg in recent studies.…”
Section: Dose-dependent Responsesupporting
confidence: 93%
“…The mechanisms that link elevated SUA levels and gout with cardiovascular comorbidities seem to be multifactorial, implicating low-grade systemic inflammation and xanthine oxidase (XO) activity, as well as the deleterious effects of hyperuricemia itself. As expected, a decrease in SUA levels has been associated with an improvement in blood pressure control, [3][4][5] as well as with some additional benefits in selected populations of patients with cardiovascular diseases (eg, coronary artery disease, heart failure, etc). 2 Most of the these favorable effects have been achieved by treating the patients with allopurinol or its derivative oxipurinol 3,4 that have have been used in the great majority of studies aimed at evaluating the cardiovascular preventive/therapeutic role of urate-lowering treatment in patients with hyperuricemia.…”
Section: See Related Article Pp 535-540supporting
confidence: 64%
“…As expected, a decrease in SUA levels has been associated with an improvement in blood pressure control, [3][4][5] as well as with some additional benefits in selected populations of patients with cardiovascular diseases (eg, coronary artery disease, heart failure, etc). 2 Most of the these favorable effects have been achieved by treating the patients with allopurinol or its derivative oxipurinol 3,4 that have have been used in the great majority of studies aimed at evaluating the cardiovascular preventive/therapeutic role of urate-lowering treatment in patients with hyperuricemia. The same treatment has been reported to reduce all-cause and cardiovascular mortality, 5 clearly supporting a possible preventive role of SUA modulation through XO inhibition.…”
Section: See Related Article Pp 535-540supporting
confidence: 64%
“…Allopurinol was associated with suppression of atrial fibrosis and endothelial nitric oxide synthetase (eNOS) in a canine tachycardia-induced cardiomyopathy model, a potential mechanism for lowering the risk of AF 42. Other potential mechanisms include associated antioxidant action,15 anti-ischaemic action,23 reduction of left ventricular mass,21 22 improvement of endothelial function16–19 and reduction in blood pressure 43 44. Future studies need to characterise the mechanisms for this potentially beneficial effect of allopurinol related to the risk of AF.…”
Section: Discussionmentioning
confidence: 99%